Analisis Penilaian Kinerja Supplier Kain dengan Menggunakan Metode Simple Additive Weighting (SAW) dan Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) (Studi Kasus: NTHM Apparel Indonesia) - Muhammad Surya Saputra; Eli Mas’idah (PT. Hasba Edukasi Mandiri, 2025)
Suppliers play a crucial role in ensuring smooth production. Supplier performance assessments are essential for prioritizing and mitigating the risk of delays. NTHM Apparel Indonesia, a custom jersey manufacturer with a Make-to-Order system, frequently faces challenges when raw materials run out, particularly when suppliers are out of stock or late in delivering, resulting in production delays. This situation forces the company to choose suppliers with stock without considering price due to time constraints. This leads to greater reliance on a few suppliers with limited stock and order queues with other companies. This study assessed five fabric suppliers (Bandung, Solo, Jogja, Wonosobo, Semarang) based on seven criteria: quality, delivery, warranty/claim, price, reciprocal agreements, communication system, and availability of raw material stock using the SAW and TOPSIS methods. The results showed that the Jogja supplier received the highest score (0.78061), making it the top priority, followed by Bandung (0.571858), Solo (0.526222), Semarang (0.472904), and finally Wonosobo (0.297241).